Pengembangan LKPD berbasis etnomatematika motif kain tenun Sambas untuk memfasilitasi kemampuan pemahaman konsep matematis siswa - Andriani, Selvy; Prihatiningtyas, Nindy Citroresmi; Mariyam, Mariyam (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
This study aims to: 1) find out the results of needs analysis in developing LKPD; 2) find out the results of the development of LKPD; 3) determine the feasibility of LKPD in terms of validity, practicality and effectiveness. The research method used is Research and Development with the ADDIE development model. The LKPD test subjects were 24 students at SMP N 1 Selakau Timur. Data analysis techniques using validity, practicality and effectiveness analysis. The results of the study show that: 1) the results of the needs analysis on LKPD, a) the analysis of students' needs shows that teachers and students want teaching materials that can help in learning mathematics. b) curriculum analysis shows that the resulting LKPD is adapted to the 2013 curriculum. c) material analysis shows that the developed LKPD is rectangular material integrated with culture; 2) the results of the development of the LKPD resulted in 2 forms of design, (a) the first design/initial draft was the initial draft of the LKPD which was the result of the researcher's study. (b) The second design is the result of a revision of the initial draft based on expert validation and student readability tests. 3) LKPD Feasibility results, namely a) LKPD is declared valid because it obtains an average value of 50 with valid information, b) LKPD is declared practical based on the results of students' responses to the use of LKPD by obtaining an average response value of 50.21 with information the response was very good, c) the LKPD was declared effective because it obtained a mastery score in learning mathematics above the KKM (Minimum Completeness Criteria)